Whom is political science for? - Andrea Theocharis; Marcus Graetsch (Politikon, 2001)
We all study political science, but - what do we actually do here anyway? This essay expresses our thoughts about our subject. The everyday life in University doesn’t seem to give enough space for questioning what is this all about. Maybe a debate on that issue does not exist extensively because of fears of the loss of entitlement. The aim of this essay is to support the heightening of student’s awareness about the status quo of research and teaching in political science as we can judge it from our modest experiences. Trying to get to the basis of such a problem is not easy. The things here written are surely not the state of the art, but they could shine a better light on the problem what had been called the 'politics of political science' in an earlier Internet discussion on the IAPSS website. This paper should be understood as a start for a discussion, where we all can express our surely different experiences and ideas.